Appearance Management as an indicator of the self-concept of NIA road male adolescents. - Polidario, Genalyn Ruby B.
The study aims to make a connection between appearance management and the self-concept. It was hoped that a tool for the rehabilitation and assimilation of juvenile delinquent into "proper" society would present itself. Selected as the target are for data gathering and research was an urban-poor (squatter) area in Quezon City called NIA Road. The problem to be resolved was whether appearance management was a good indicator of the self-concept for male adolescents living in NIA Road. That is, whether good appearance is indicative of a positive self-concept and vice versa. Data needed for the study was gathered through surveys, making use of separate instruments for appearance management and self-concept. The Multi-Stage Cluster sampling design was used. Fifty-nine sample were gathered over the five NIA Road Areas. Resulting data from both instruments were turned over to the U.P. Statistical Center for statistical analysis to determine the degree of association between appearance management and self-concept. The statistical analysis showed that appearance management was found to have a significant correlation with self-concept in that as appearance management scores go up, self-concept scores also tend to go up. This means that an improvement in appearance management may mean a boost to a low self-concept. Through survey data was limited, it affirmatively indicates that we may have a useful tool for boosting the self-concept of afflicted adolescents. Similar and more extensive studies with better survey instruments in other urban-poor communities could come up with more definitive findings.